Global warming and East Asia : the domestic and international politics of climate change - Harris, Paul G. (Routledge research in environmental politics ;, 2003)
Examines the domestic politics, foreign policy and international relations of climate change in China, Japan and Southeast Asia, often disproportionately affected; increasing our understanding of a region vital to mitigating and coping with climate.